Delivery strategies and potential targets for siRNA in major cancer types - Lee, So Jin; Kim, Min Ju; Kwon, Ick Chan; Roberts, Thomas M. (ELSEVIER, 2016)
Small interfering RNA (siRNA) has gained attention as a potential therapeutic reagent due to its ability to inhibit specific genes in many genetic diseases. For many years, studies of siRNA have progressively advanced toward novel treatment strategies against cancer. Cancer is caused by various mutations in hundreds of genes including both proto-oncogenes and tumor suppressor genes. In order to develop siRNAs as therapeutic agents for cancer treatment, delivery strategies for siRNA must be carefully designed and potential gene targets carefully selected for optimal anti-cancer effects. In this review, various modifications and delivery strategies for siRNA delivery are discussed. In addition, we present current thinking on target gene selection in major tumor types. (C) 2016 Elsevier B.V. All rights reserved.